Introducing a New Technique for Fascial Closure to Avoid Renal Allograft Compartment Syndrome in Pediatric Recipients: The Use of Tutoplast® Fascia Lata - Bañuelos Marco, Beatriz; Bergel, Berenice; Geppert, Tamara; Müller, Dominik; Lingnau, Anja (Frontiers in Surgery, 2022)
Introduction Renal allograft compartment syndrome (RACS) is a complication that infrequently occurs after kidney transplantation. Tight muscle closure may lead to RACS due to compression of renal parenchyma or kinking of the renal vessels. Many techniques have been proposed in an attempt to achieve tension-free closure, which can be specially challenging in children recipients. We present our experience with Tutoplast® Fascia Lata closure. Methods All paediatric patients who underwent kidney transplantation in our centre between 2012 and 2021 were reviewed. Eight patients with Tutoplast® Fascia Lata placed at the time of initial transplantation were identified. Donor and recipient characteristics, Doppler ultrasound findings, and overall patient and graft survival rates were analysed. Results Doppler ultrasound was performed intra operatively after abdominal wall closure. If any sign of vascular compromise was seen the abdominal wall was opened and the graft revised. The Tutoplast® Fascia Lata implant was used to perform tension-free fascia closure and afterwards a Doppler ultrasound was performed to confirm the optimal renal artery perfusion and venous patency. Three of the kidney transplantations were from cadaver donor, being 2 of them en bloc. Living donor was performed in four cases and there was a case of auto-transplantation due to bilateral renal artery stenosis. None of the patients presented any complication, either short term or long term derived from the abdominal closure with Tutoplast® Fascia Lata and there was no record of graft failure till datum. Conclusions Restricted volume of the recipient pelvic cavity and the size discrepancy between the recipient pelvic cavity space and the donor adult kidney may lead to RACS. Other situation occurring more infrequently such us en bloc or auto-transplantation are prone to suffer the same problem. Tutoplast® Fascia Lata is a safe option for these patients.